The Development of Illustrated Storybook Media Based on Balantak Local Wisdom to Enhance Early Childhood Character - Sunyin Sengang; Andi Agusniatih; Sita Awalunisa; Durrotunnisa Durrotunnisa (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Early childhood is a critical period for shaping character through appropriate educational media. This study aims to develop and determine the feasibility of an illustrated storybook based on Balantak local wisdom to enhance the character of children aged 5ÔÇô6 years. The research was conducted at TK Sejahtera Bonebak, involving all Group B children as participants. The method used was Research and Development (R&D) with the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The study specifically aimed to produce a culturally relevant storybook and assess its suitability in supporting children's character development. Feasibility was assessed by a language expert and a media expert, resulting in scores of 95.4% and 94.4%, both classified as highly valid. The storybook was tested on children focusing on four character traits: courage, discipline, tolerance, and social care. The results showed that the media was highly feasible and effectively supported the development of these character traits. In conclusion, illustrated storybooks incorporating local wisdom can serve as effective tools for character education in early childhood settings.┬á┬á